On the Borders of World-Systems - Margaryan, Yervand (Archaeopress, 2020)
This work examines the historical, archaeological, and political interpretations of world-systems theory and geocivilizational analysis. The macrosociological issues of ancient and modern history are presented through five case-studies, concentrating on the Taurus-Caucasus region, which functioned as a contact zone throughout the different periods.